Injury Occurrence in Break Dance: An Online Cross-Sectional Cohort Study of Breakers. Issue 1 (March 2021) - Tsiouti, Nefeli; Wyon, Matthew
Breaking is the most physical of the hip-hop dance styles, but little research has examined the health and well-being of its participants. Using a cross-sectional recall design, a self-reported online health and well-being survey was open for a 5-month period (April 2017 to August 2017). Tree hundred and twenty adult break dancers (16% professional, 65% student-recreational) with a minimum of 6-months experience completed the survey. The main outcome measures were injury incidence and etiology and training hours. Fifty-two percent of respondents trained between 4 and 9 hours per week over 3 days, which is significantly less than theatrical dancers. More than 71% reported a dance-related injury in the previous 12 months, and 44.5% were injured at time of the survey. Self-reported types of injury were significantly different from other dance genres. The most frequently injured body parts were arm-hand (40.6%), shoulder (35.9%), knee (32.2%), neck (22.8%), and ankle (15.6%). When injured, 29% of respondents either took their own preventative steps or continued to dance carefully, while 20% sought medical help. "Yourself" was the most cited influence on returning to dance after injury (47%). The current survey highlights breaking's differences from other dance genres, particularly with regard to injury incidence and etiology.